EFFECTIVENESS OF BAKUNG EXTRACT (CRINUM ASIATICUM L) AS AN ANALGESIC IN ACETIC ACID-INDUCED MICE - Teodhora Simangunsong; Elzius Fransiscus Lumban Gaol; Sister Sianturi (Jurnal Farmasi Sains dan Praktis, 2021)
Crinum asiaticum L. leaves is a plant that has a pharmacological effect, which is to relieve pain. The purpose of this study was to determine the effect of the ethanol extract of daffodils as an analgesic effect on male mice DDY. The extract was obtained through the maceration extraction method and was administered by oral administration with three dose variations, namely 200 mg/kg BW, 400 mg/kg BW, and 800 mg/kg BW. Ibuprofen 52 mg/kgBW was used as a positive control and Na-CMC 0,5% as a negative control. 30 minutes after induced with 1% acetic acid the amount of stretching was observed every 5 minutes to 60 minutes. The results showed the best analgesic effect at dose III 800 mg/kg BW with the percentage of analgesic protection of 80,66%. The results of effectiveness at dose III 800 mg/kg BW of 99,37% which is almost the same as the effectiveness of Ibuprofen at a dose of 52 mg/kgBW of 100%